1984
DOI: 10.1038/308653a0
|View full text |Cite
|
Sign up to set email alerts
|

Release of the predicted calcitonin gene-related peptide from cultured rat trigeminal ganglion cells

Abstract: Calcitonin gene-related peptide (CGRP) is a putative novel neuropeptide predicted on the basis of alternative RNA processing events of primary transcripts of the calcitonin gene. Distinct mRNAs encoding either calcitonin or CGRP are generated from the calcitonin gene RNA transcript in what appears to be a tissue-specific manner. The predicted peptide has now been detected immunocytochemically in discrete regions of the central and peripheral nervous systems and potent in vivo actions have been reported for cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(71 citation statements)
references
References 7 publications
5
66
0
Order By: Relevance
“…Physiological experiments have shown that antidromic stimulation of nerve fibers derived from the trigeminal sensory ganglion induces an increase in the content of pulpal substance P (OLGART et al, 1977), which is colocalized in the CGRP-containing nerve fibers (WAKISAKA et al, 1987), and also increases pulpal blood flow (GAZELIUS and OLGART, 1980). Furthermore, stimulation of trigeminal sensory neurons has demonstrated the antidromic release of CGRP in vitro (MASON et al, 1984). It is thus reasonable that CGRP is in possible collaboration with substance P released from nerves to act as vasodilator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological experiments have shown that antidromic stimulation of nerve fibers derived from the trigeminal sensory ganglion induces an increase in the content of pulpal substance P (OLGART et al, 1977), which is colocalized in the CGRP-containing nerve fibers (WAKISAKA et al, 1987), and also increases pulpal blood flow (GAZELIUS and OLGART, 1980). Furthermore, stimulation of trigeminal sensory neurons has demonstrated the antidromic release of CGRP in vitro (MASON et al, 1984). It is thus reasonable that CGRP is in possible collaboration with substance P released from nerves to act as vasodilator.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic of CGRP-immunoreactive nerve terminals suggests diverse functions for the mitochondria-rich nerve endings. Trigeminal sensory nerves possess the potential for antidromic release of CGRP (MASON, 1984), and CGRP manifests multiple functions such as trophic effects on vascular smooth muscle cells, fibroblasts and lymphocytes, as well as vascular effects (for review, HOLZER, 1988). Thus, the CGRPpositive nerve terminals associated with odontoblast may also be involved in some active-such as trophic -functions in addition to the receptive function .…”
Section: Discussionmentioning
confidence: 99%
“…CGRP is released by rat trigeminal ganglion cells in vitro (Mason et al, 1984) and it seems likely that CGRP may act as a neurotransmitter or neuromodulator. The distribution of CGRP in the spinal cord is similar to that of SP and suggests a sensory role for this peptide (Gibson et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…CGRP-immunoreactivity is found in heart particularly around the sinoatrial and atrioventricular node, as well as in periadventitial nerves in association with blood vessels (Manson et al, 1984;Wisenfeld-Hallin et al, 1984;Mulderry et al, 1985;Gennari & Fischer, 1985).…”
Section: Introductionmentioning
confidence: 99%